2002
DOI: 10.1038/modpathol.3880504
|View full text |Cite
|
Sign up to set email alerts
|

c-kit Mutations in Gastrointestinal Stromal Tumors Occur Preferentially in the Spindle Rather Than in the Epithelioid Cell Variant

Abstract: Gastrointestinal stromal tumors (GISTs) coexpress CD34 and the Kit tyrosine-kinase receptor (CD117). A subset of GISTs carry gain-of-function mutations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0
7

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 25 publications
8
71
0
7
Order By: Relevance
“…5 In addition, the prevalence of the spindle-cell type of GISTs might influence the low frequency of PDGFRA gene mutation in the current study, because, in general, PDGFRA mutation is more frequently present in epithelioid-cell type GISTs than in spindle-cell type GISTs (most of our cases were spindle-cell type). 41 In conclusion, we found that MVD was correlated with both VEGF overexpression and worse prognosis in GISTs. Our results suggest that angiogenesis measured as MVD is useful for predicting the aggressive biologic behavior of GIST, and that angiogenesis associated with VEGF may play an important role, at least in part, in the progression of GIST.…”
Section: Factorsmentioning
confidence: 57%
“…5 In addition, the prevalence of the spindle-cell type of GISTs might influence the low frequency of PDGFRA gene mutation in the current study, because, in general, PDGFRA mutation is more frequently present in epithelioid-cell type GISTs than in spindle-cell type GISTs (most of our cases were spindle-cell type). 41 In conclusion, we found that MVD was correlated with both VEGF overexpression and worse prognosis in GISTs. Our results suggest that angiogenesis measured as MVD is useful for predicting the aggressive biologic behavior of GIST, and that angiogenesis associated with VEGF may play an important role, at least in part, in the progression of GIST.…”
Section: Factorsmentioning
confidence: 57%
“…9,10,18 Activating mutations within the KIT gene were detected in 57-92% of GISTs in earlier reports. [9][10][11][12][13]16 The frequency of KIT mutations in our series was apparently lower in epithelioid than in mixed and spindle type GISTs. Previous reports have already suggested that the frequency of KIT mutations in epithelioid GISTs may be lower than in spindle cell variants.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports have already suggested that the frequency of KIT mutations in epithelioid GISTs may be lower than in spindle cell variants. Accordingly, Wardelmann et al 16 reported no KIT mutations in seven GISTs with an epithelioid component, while all 21 GISTs with detectable KIT mutations displayed a spindle cell phenotype. This finding was supported by a more recent study 13 that included 19 epithelioid GISTs and only six of which harbored KIT mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic and therapeutic significance of KIT mutations is somewhat contradictory (Ernst et al, 1998;Lasota et al, 1999;Moskaluk et al, 1999;Taniguchi et al, 1999;Lasota et al, 2000;Hirota et al, 2001;Wardelmann et al, 2002;Koay et al, 2005). Therefore, it appears that new molecular indicators of prognostication are needed.…”
mentioning
confidence: 99%